Utilization of Posyandu Services and its Relationship with Stunting in 6–24-Month Old Children - Nurmawaddah, Intan; Nurbaiti, Lina; Paramaiswari, Nurul Firdausi (Jurnal Biologi Tropis, 2025)
Stunting is still a serious public health concern in Indonesia, especially in places with poor access to medical care. Stunting risk is thought to be significantly decreased by using Posyandu services, which include exclusive breastfeeding, full basic immunization, and appropriate reporting in the Maternal and Child Health (KIA) Book. Ninety respondents were chosen by stratified random sampling for this cross-sectional observational analytical study. Bivariate statistical analysis was conducted to examine the relationships between exclusive breastfeeding, basic immunization, and KIA Book completeness with stunting. The results showed no significant association between exclusive breastfeeding and stunting (p = 0.687), basic immunization and stunting (p = 0.079), or KIA Book completeness and stunting (p = 0.665). Although immunization coverage was higher among stunted children (93% versus 80%) and KIA Book completeness was high in both groups (98% in stunted versus 96% in non-stunted), these differences were not statistically significant. In conclusion, exclusive breastfeeding, basic immunization, and KIA Book documentation were not significantly associated with stunting in children attending the Puyung Health Center, Central Lombok Regency. Further studies are recommended to explore the roles of nutrition, parenting practices, and socioeconomic factors in the occurrence of stunting.